2020
DOI: 10.3390/jcm9113661
|View full text |Cite
|
Sign up to set email alerts
|

Root Canal Transportation after Root Canal Preparation with ProTaper Next, WaveOne Gold, and Twisted Files

Abstract: Background: Root canal preparation during endodontic treatment may be associated with various complications, including a change in the original pathway of the root canal lumen. The aim of our study was to determine whether files of similar sizes that use various movement kinematics (rotary, reciprocal, adaptive motion) cause root canal transportation, and whether the differences between such systems are statistically significant. Methods: The degree of root canal transportation (DT) was calculated with the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Root canal treatment procedures constitute a significant part of dental treatment provided worldwide, and allow patients to retain their natural dentition with a success rate similar to implant placement procedures [ 1 , 2 ]. However, various complications may occur during its all stages, including perforation, change in the original path of the root canal, instrument fracture, all of which may make it impossible for the clinician to achieve the primary aim of treatment, i.e., infection control and disinfection of the root canal space [ 3 , 4 ]. Apical extrusion of debris is another example of such complication, and it has been proven to be an unavoidable occurrence during endodontic treatment by numerous authors since the methodology for measuring the amount of extruded material was introduced by Myers and Montgomery in 1991 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Root canal treatment procedures constitute a significant part of dental treatment provided worldwide, and allow patients to retain their natural dentition with a success rate similar to implant placement procedures [ 1 , 2 ]. However, various complications may occur during its all stages, including perforation, change in the original path of the root canal, instrument fracture, all of which may make it impossible for the clinician to achieve the primary aim of treatment, i.e., infection control and disinfection of the root canal space [ 3 , 4 ]. Apical extrusion of debris is another example of such complication, and it has been proven to be an unavoidable occurrence during endodontic treatment by numerous authors since the methodology for measuring the amount of extruded material was introduced by Myers and Montgomery in 1991 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result agrees with Gajoum et al (2021) 3 who found that PTN was statistically significantly greater than WOG system in terms of canal transportation. Also, Eliasz et al (2020) 30 who found that PTN produced more transported canal preparation when compared with WOG and twisted file. This increase in transportation could be due to the metallurgical features of the file; M-wire does have more file memory compared to WOG thus straightening the canal more.…”
Section: Asdj Ain Shams Dental Journalmentioning
confidence: 99%
“…After preparation, irrigation with 5 ml of ethylenediaminetetraacetic acid (EDTA) in concentration of 17% for 60 seconds was performed for debris removal. (17) Afterwards, obturation with gutta-percha and root canal sealer (MetaBiomed resin sealer) was done using lateral condensation technique. A heated plugger was then used to remove two millimetres of the filling at the area below the cementoenamel junction and then covered with 1 mm thick resinmodified glass-ionomer cement (GC-FUGI, Tukyo, Japan) for cervical seal.…”
Section: Endodontic Treatmentmentioning
confidence: 99%